Straßen sind keine Splines (mathematica didactica, 2005)
Curve sketching is a classic element of the everyday math lessons. Many of the traditional tasks, however, have become questionable due to the introduction of functionplotters and computer algebra systems, and are gradually replaced by new tasks. Thus, the task of “route planning” has been established by now. In this article we trace the introduction of this task in the math lessons and discuss their relationship to reality.